EFFECT OF MANGO (Mangifera indica) CV. AZÚCAR JUICE CONSUMPTION ON PLASMA ANTIOXIDANT CAPACITY AND OXIDATIVE STRESS BIOMARKERS - Zapata, Maria bibiana; Ramos Polo, Ana; Alzate, Andres Felipe; Restrepo Betancur, Luis Fernando; Rojano, Benjamin; Maldonado, Maria Elena (Vitae, 2020)
Background: Mango (Mangifera indica L.) is one of the world’s most consumed fruit, and it is also a rich source of antioxidants that may prevent oxidative stress. Objectives: This study aimed to determine if mango (cv. Azúcar) juice can improve the antioxidant status of healthy individuals with low consumption of vegetables and fruit. Methods: This was a cross-over single-blind study carried out with 16 healthy individuals for 73 days. Participants were randomly assigned to either a mango juice period or a placebo period. Total phenolic content, antioxidant capacity, mangiferin, thiobarbituric acid reactive substances (TBARS), total glutathione, and 8-hydroxydeoxyguanosine levels were determined in plasma. Results: Plasma antioxidant activity was significantly higher in the juice consumption period than the placebo consumption period; however, total phenolic content, total glutathione, TBARS, and 8-hydroxydeoxyguanosine levels did not show significant differences between juice period and placebo period. Mangiferin was detected in every participant after juice consumption. Conclusions: Mango (cv. Azúcar) juice daily consumption improves plasma antioxidant capacity.